EVALUATION OF PHYSICAL EDUCATION LEARNING IN PRIMARY SCHOOL - Moch. Asmawi; Johansyah Lubis; Juditya S; Zakaria D A; Rony Mohamad Rizal (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
Evaluation is an important part in the learning series, as well as in the physical education learning series. Even from the evaluation process carried out in schools, a teacher will get a picture of the learning achievement. Therefore, the purpose of this study is to determine the level of perception, understanding, application and achievement of the process carried out by physical education teachers at the primary school level in the evaluation of physical education learning. The method used is descriptive quantitative with a survey approach. The instrument used in the form of a questionnaire (questionnaire) distributed to all physical education teachers in SD in Cibiru District, totaling 30 people. The data analysis technique used quantitative descriptive analysis as outlined in percentages and the results of this study showed that the level of perceptions of physical education teachers in the evaluation of physical education learning in elementary schools in Cibiru District was 6.67% (2 teachers) in the very high category, 26 , 66% (8 teachers) in the high category, 36.67% (11 teachers) in the medium category, 23.33% (7 teachers) in the low category and 6.67% (2 teachers) in the very low category. Thus it can be concluded that most of the physical education teachers' perceptions of the evaluation of physical education learning in SDs in Cibiru District, Bandung City are moderate with the amount of 36.67%.